Primary epidermoid carcinoma of the breast presenting as a breast abscess and sepsis - Damin, Andrea Pires; Nascimento, Fernanda Costa; Andreola, João Batista; Cerutti, Talita Haubert; Roehe, Adriana; Damin, Daniel Carvalho (São Paulo Medical Journal, 2011)
CONTEXT: Squamous cell carcinoma (SCC) of the breast is an extremely rare form of cancer, accounting for approximately 0.04% of all malignant breast tumors. To date, only a limited number of cases of SCC of the breast have been reported, and most of them presented like the usual breast carcinomas. CASE REPORT: A 39-year-old woman presented with a large breast abscess and signs of sepsis. After surgical debridement of the lesion, histopathological examination of the abscess capsule revealed the presence of SCC of the breast. The definitive treatment for the tumor consisted of modified radical mastectomy with resection of the residual lesion in the right breast. CONCLUSIONS: This unusual case illustrates how an apparently benign disorder such as a breast abscess might be related to a clinically occult malignancy. A review of the literature on SCC of the breast is presented.